Reduction of hydrogen absorption into materials of membrane electrode assemblies in hydrogen generators - M. V. Lebedeva; A. V. Ragutkin; I. M. Sidorov; N. A. Yashtulov (Тонкие химические технологии)
Objectives. To investigate the possibility of preventing hydrogen absorption into the functional structural materials of hydrogen-generating membrane electrode assemblies based on porous nickel, carbon black, and reduced graphene oxide with platinum–nickel and palladium–nickel nanoparticles.Methods. The hydrogen absorption into materials of membrane electrode assemblies of alkaline electrolyzers was evaluated using an electrolyzer with variable temperature, reagent feed rate, and gas content.Results. The study established the need to use reduced graphene oxide, in order to reduce hydrogen absorption and degradation of hydrogen-generating membrane electrode assemblies.Conclusions. The service life test results and performance of the designed variants of prototypes of membrane electrode assemblies with nanostructured electrodes based on reduced graphene oxide, preventing hydrogen absorption into functional materials and their degradation, demonstrated the creation of hydrogen generators with high energy efficiency shows potential.